Comparing treatment uncertainty for ultra- vs. standard-hypofractionated breast radiation therapy based on in-vivo dosimetry. (April 2022) - Fiagan, Yawo A.C.; Bossuyt, Evy; Machiels, Melanie; Nevens, Daan; Billiet, Charlotte; Poortmans, Philip; Gevaert, Thierry; Verellen, Dirk
Abstract: Background and purpose: Postoperative ultrahypofractionated radiation therapy (UHFRT) in 5 fractions (fx) for breast cancer patients is as effective and safe as conventionally hypofractionated RT (HFRT) in 15 fx, liberating time for higher-level daily online Image-Guided Radiation Therapy (IGRT) corrections. In this retrospective study, treatment uncertainties occurring in patients treated with 5fx (5fx-group) were evaluated using electronic portal imaging device (EPID)-based in-vivo dosimetry (EIVD) and compared with the results from patients treated with conventionally HFRT (15fx-group) to validate the new technique and to evaluate if the shorter treatment schedule could have a positive effect on the treatment uncertainties. Materials and methods: EPID-based integrated transit dose images were acquired for each treatment fraction in the 5fx-group (203 patients) and on the first 3 days of treatment and weekly thereafter in the 15fx-group (203 patients). A total of 1015 EIVD measurements in the 5fx-group and 1144 in the 15fx-group were acquired. Of the latter group, 755 had been treated with online IGRT correction (i.e., Online-IGRT 15fx-group). Results: In the 15fx-group 12.0% of fractions failed (FFs) compared to 3.8% in the 5fx-group and 6.9% in the online-IGRT 15fx-group. Causes for FFs in the 15fx-group compared with the 5fx-group were patient positioning (7.4% vs. 2.2%), technical issues (3.1% vs. 1.2%) and breast swelling (1.4% vs. 0.5%). In the online-IGRT 15fx-group, 2.5% were attributed to patient positioning, 3.8% to technical issues and 0.5% to breast swelling. Conclusions: EIVD demonstrated that UHFRT for breast cancer results in less FFs compared to standard HFRT. A large proportion of this decrease could be explained by using daily online IGRT.